Magneto-optical diagnosis of symptomatic malaria in Papua New Guinea - L. Arndt (Nature Portfolio, 2021)
Here Arndt et al. establish rotating-crystal magneto-optical detection (RMOD) as a near-point-of-care diagnostic tool for malaria detection and report a sensitivity and specificity of 82% and 84%, respectively, as validated by analyzing a clinical population in a high transmission setting in Papua New Guinea.